2020
DOI: 10.3390/vaccines8010082
|View full text |Cite
|
Sign up to set email alerts
|

MVA Vectored Vaccines Encoding Rift Valley Fever Virus Glycoproteins Protect Mice against Lethal Challenge in the Absence of Neutralizing Antibody Responses

Abstract: In vitro neutralizing antibodies have been often correlated with protection against Rift Valley fever virus (RVFV) infection. We have reported previously that a single inoculation of sucrose-purified modified vaccinia Ankara (MVA) encoding RVFV glycoproteins (rMVAGnGc) was sufficient to induce a protective immune response in mice after a lethal RVFV challenge. Protection was related to the presence of glycoprotein specific CD8+ cells, with a low-level detection of in vitro neutralizing antibodies. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Another study showed the cooperative effect of a non-neutralizing antibody improving protection in a mouse model ( Gutjahr et al., 2020 ). Perhaps more surprisingly, mice vaccinated with modified Vaccinia Ankara (MVA) expressing both Gn and Gc failed to elicit nAbs but were still protected from viral challenge ( Lopez-Gil et al., 2020 ). IgG1, the predominant subclass recognizing the RVFV glycoproteins identified here, can efficiently trigger the classical route of complement ( Vidarsson et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed the cooperative effect of a non-neutralizing antibody improving protection in a mouse model ( Gutjahr et al., 2020 ). Perhaps more surprisingly, mice vaccinated with modified Vaccinia Ankara (MVA) expressing both Gn and Gc failed to elicit nAbs but were still protected from viral challenge ( Lopez-Gil et al., 2020 ). IgG1, the predominant subclass recognizing the RVFV glycoproteins identified here, can efficiently trigger the classical route of complement ( Vidarsson et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…They were equally distributed into groups of 5–7 animals and inoculated intraperitoneally with 500 plaque-forming units (pfus) of the corresponding viruses. Development of disease was evaluated over 3 weeks (18 days) in terms of mortality and morbidity, as elsewhere [ 18 ] checking for weight and development of clinical signs, such as ruffled fur, ocular discharges, hunched posture and reduced activity. Blood samples were collected in Microvette ® tubes K3 EDTA or Serum (Sarstedt, Nümbrecht, Germany) upon submandibular puncture at 72 h after infection and tested for viral RNA by RT-qPCR [ 16 , 19 ] to monitor viremia, while serum samples collected from survivor mice at the end of the experiment (day 18 pi) were used in antibody assays.…”
Section: Methodsmentioning
confidence: 99%
“…Wild-type rZH548 (red) and rZH548∆NSs::GFP (labeled as, rZH∆NSs/GFP, green) viruses were included as controls for virulence and attenuation, respectively. Animals were monitored up to18 days. (A) Survival rates and (B-E) morbidity upon challenge with the indicated viruses.…”
mentioning
confidence: 99%
“…Another study showed the cooperative effect of a non-neutralizing antibody improving protection in a mouse model (Gutjahr et al, 2020). Perhaps more surprisingly, mice vaccinated with modified Vaccinia Ankara (MVA) expressing both Gn and Gc failed to elicit nAbs but were still protected from viral challenge (Lopez-Gil et al, 2020). IgG1, the predominant subclass recognising the RVFV glycoproteins identified here, can efficiently trigger the classical route of complement (Vidarsson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%